Evolución de la producción azucarera en el distrito de el general, pérez zeledón, entre la segunda mitad del siglo XIX y la década de 1970 - Durán Barrantes, Norman Dimas (Revista de historia., 2006)
This article deals on the origin and evolution of the sugar cane production line in the district EI General. Perez Zeled6n, between the second half of XIX century and the middle 1970’s. The article analyzes from a regional history perspective the development routes used by the producers in the agricultural border to establish the basis of sugar cane activity in the south of Costa Rica; as well as the impact which had technical and organizational changes on the industry foundations of sugar in this part of the country.